2011
DOI: 10.1016/j.bbrc.2011.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Clustered hydrophobic amino acids in amphipathic helices mediate erlin1/2 complex assembly

Abstract: Erlin1 and erlin2 are highly homologous, ~ 40kDa, endoplasmic reticulum membrane proteins that assemble into a ring-shaped complex with a mass of ~2MDa. How this complex is formed is not understood, but appears to involve multiple interactions, including a coiled-coil region that mediates lower-order erlin assembly, and a short hydrophobic region, termed the “assembly domain”, that mediates higher-order assembly into ~2MDa complexes. Here we have used molecular modeling, mutagenesis and cross-linking to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Importantly, these proteins were previously demonstrated to participate in ER-to-cytosol membrane penetration of SV40 [ 5 , 19 , 20 ]. Also included in this list are Erlin1 and Erlin2 (Erlin1/2), two closely related ER membrane proteins that hetero-oligomerize to form a massive protein complex [ 25 , 26 , 28 ]. Because Erlin1/2 have been implicated in an ER-to-cytosol transport-dependent protein quality control process called ER-associated degradation [ 27 , 29 , 30 ], we decided to focus on these proteins since SV40 similarly undergoes ER-to-cytosol transport.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, these proteins were previously demonstrated to participate in ER-to-cytosol membrane penetration of SV40 [ 5 , 19 , 20 ]. Also included in this list are Erlin1 and Erlin2 (Erlin1/2), two closely related ER membrane proteins that hetero-oligomerize to form a massive protein complex [ 25 , 26 , 28 ]. Because Erlin1/2 have been implicated in an ER-to-cytosol transport-dependent protein quality control process called ER-associated degradation [ 27 , 29 , 30 ], we decided to focus on these proteins since SV40 similarly undergoes ER-to-cytosol transport.…”
Section: Resultsmentioning
confidence: 99%
“…When Erlin1/2 is depleted, we found that endogenous B12 can mislocalize to the nucleus ( Fig 9 ), suggesting that Erlins act as anchors, restricting B12 in the ER. Because Erlin1/2 have been shown to hetero-dimerize and form massive megadalton protein complexes [ 26 28 ], this intrinsic property may enable them to function as efficient anchoring factors. Consistent with this, another group demonstrated that overexpressed WT B12 similarly mislocalizes to the nucleus and forms nuclear globular structures termed DJANGOS [ 35 ], presumably due to insufficient levels of Erlins that are required to restrict the overexpressed proteins in the ER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On this regard, Browman et al [29] focused on the identification and characterization of two novel proteins preferentially enriched in lipid raft fractions from ER fractions of myelomonocytic cells: ERLIN1/KE04 (ER lipid raft associated 1) and ERLIN2/C8orf2 (ER lipid raft associated 2), proposed as the most recently discovered members of the prohibitin family of proteins. ERLIN1 and ERLIN2 are highly homologous and hetero-oligomerize to form a massive protein complex of ~40 subunits in lipid rafts [30,31]. A well-defined function of this complex is to mediate the ubiquitination of activated ITPRs (inositol 1,4,5-trisphosphate receptors) and then their degradation [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Such proteins are found in the cytoplasm or the ER and have a broad range of important biological functions. For example, such structures are used in the cell for measuring membrane curvature [47] , for generating membrane vesicles [48] , [49] , or for establishing protein-protein interactions [50] . The amphipathic helices are generally oriented parallel to the membrane surface and act, in the case of proteins involved in the budding of membrane vesicles, as a membrane anchor of these proteins.…”
Section: Discussionmentioning
confidence: 99%